Peran Galeri Investasi Syariah Dalam Menumbuhkan Minat Mahasiswa Untuk Melakukan Investasi Di Pasar Modal Syariah : Studi Kasus Pada Galeri Investasi Syariah FEBI UIN STS Jambi - Dora Rahmayeni; Ahsan Putra Hafiz; Awal Habibah (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research is motivated by the role of the Sharia Investment Gallery (GIS) as a student laboratory for learning about investment. Based on the data, the number of investors in the Islamic Investment Gallery from the inception of GIS from 2016 to 2021 is unstable every year and is still relatively low. Even though the FEBI Faculty has good potential in attracting investors because there are so many enthusiasts in the FEBI departments. Low interest and motivation in investing in Indonesia is due to low knowledge and understanding of the capital market. GIS is expected to help foster student interest in investing in the Islamic capital market. The purpose of this study was to determine the role of Gis, both the constraints and solutions faced by Gis in fostering students' interest in investing in the capital market. This research approach uses descriptive method with a descriptive qualitative approach, namely research that seeks to describe a symptom, event, event that is happening now. The method used in this research is to collect data through interviews, observation, surveys, and documentation. The results of the study show the role of Islamic investment galleries (GIS) in fostering student interest in investing in the capital market by carrying out 4 roles, namely first, socialization as an introduction to the world of investment to students and inviting students to invest, second education, namely providing investment knowledge to students, third motivation, namely motivating students by giving examples of people who are successful in investing, the four integrity, namely the management of GiS applies a commitment attitude among the board, consistently carrying out their duties, being responsible, honest and courageous in conveying educational and motivational socialization to students. The internal constraints for Gis are the difficulty of coordinating administrators to be active in activities and the external constraints are the difficulty in getting students to participate in Gis activities and the lack of awareness of students to invest. The internal solution is to always hold monthly meetings to strengthen relationships between administrators and trigger back responsibilities as GIS administrators and the GIS Management also utilizes social media as a promotional medium so that it can be even wider to convey socialization and education to students. Meanwhile, for external solutions, GIS requests lecturer assistance to direct students to participate in all activities held by GIS. As for these 4 roles, the role most expected by FEBI students is the role of motivation. With good motivation given it can trigger students’ interest in investing.